Assessment of the Australian digital cadastre protocol (ePlan) in terms of supporting 3D building subdivisions. (November 2016) - Shojaei, Davood; Olfat, Hamed; Rajabifard, Abbas; Darvill, Ashley; Briffa, Mark
Highlights: Australian digital cadastre protocol (ePlan) was examined in terms of 3D spatial unit modelling. Various simple and complex building subdivision plans were investigated and modelled in ePlan. An efficient approach for modelling 3D spatial units in ePlan is proposed. The ePlan Protocol is able to support 3D building subdivision plans. In the ePlan Protocol, curved shapes are not well handled. Abstract: Population growth and lack of available land in urban areas have resulted in intensive property development both above and below ground. According to the 'Cadastre 2034 Strategy' published by the Intergovernmental Committee on Surveying and Mapping (ICSM) for Australia in 2014, the current digital cadastres have limitations in positional accuracy and do not adequately represent the three-dimensional nature of real property. This strategy highlights the fact that land parcels that are limited in vertical dimension are not adequately represented in the current digital cadastre. This makes it difficult to visualise security of tenure as it relates to a building or an apartment within a building. Since 2011, a national cadastral data model (ePlan Protocol) is being implemented in different Australian jurisdictions including Victoria, New South Wales and Queensland for 2D (non-building) plans of subdivision. Following the ICSM's strategy, the ePlan Working Group has started to investigate the requirements for supporting 3D building subdivisions in ePlan. As part of this investigation and to assess the potential of the ePlan Protocol in terms of supporting 3D spatial units associated with land and property management, a research project was recently undertaken in Victoria, Australia. In this research, various building subdivision plans were investigated and modelled in ePlan and a number of technical and non-technical challenges were identified. Overall, the study confirmed that the ePlan Protocol is able to support 3D building subdivision plans, however curved shapes are not well handled. This paper also proposes future investigations for implementing a 3D digital cadastre in Victoria.